Human Papillomavirus (HPV) Infection: Molecular Epidemiology, Genotyping, Seroprevalence and Associated Risk Factors among Arab Women in Qatar - Elmi, Asha A. (PLoS One, 2017)
Human Papillomavirus (HPV) infections are known to cause cervical cancer worldwide, however, limited information is currently available on prevalence, types distribution and risk factors for HPV infection in the Arab countries. We conducted a cross-sectional observational study exclusively of women of Arabic origin residing in Qatar (n = 406) who were selected from the Women’s Hospital at Hamad Medical Corporation (HMC) and Health Centers of the Primary Health Care Corporation in Doha, Qatar over the period March 2013 to August 2014. Socio-demographic, behavioral and clinical data were collected. Four hundred and six cervical smears and 292 blood samples were included in the study. HPV typing was done using HPV type-specific primers-based real-time PCR, and Sanger sequencing. HPV-IgG and IgM were quantified using ELISA assays. The prevalence of HPV infection amongst Qatari and non-Qatari Arab women were 9.8% and 6.1%, respectively and 7.6% and 16.7% in women with normal and abnormal cytology, respectively. HPV 81 was the most commonly found genotype in women with normal cytology (34.5%), whereas HPV 81, 16 and 59 in women with abnormal cytology (25.0% each). All the HPV DNA positive women were seronegative and HPV-IgG prevalence was higher in Qatari women than in non-Qatari Arab women. None of the studied factors had any significant association with HPV-DNA positivity or HPV-IgG seropositivity. The overall identified HPV DNA prevalence and HPV seroprevalence among Arab women in Qatar were on the low side compared to global levels.